VILLAGE SPACE PATTERNS ADAPTATION AS EXISTENCE RESILIENCE IN BRAGA’S URBAN VILLAGE - BANDUNG - Asri, Shirli Putri (Ide dan Dialog Desain Indonesia (Idealog), 2022)
The research issue is that the pattern of building arrangements on Jalan Braga is increasing in function, resulting in the village of Braga getting narrower. This study aims to find out the pattern of Braga village order in terms of resilience to the times, as proof of the existence of Braga village today. This study used a quantitative descriptive method, the results of the analysis were obtained by direct interviews with the residents of Braga Village. In addition, the analysis was processed using data sources through observation, literature and questionnaires. The spatial pattern of the village of Braga is formed on the basis of the history of the village. Meanwhile, settlement patterns are formed based on physical (environmental conditions), economic, social and cultural. The purpose of this research is to find out the history of Braga village, changes in the pattern of Braga village as resilience and the potential or disaster that will arise from this change in pattern. The pattern of the Braga village from the results of the analysis has an elongated pattern, this pattern occurs because the Braga village is close to the Braga road. Braga village which is close to Braga road, makes Braga village have to adapt to the current development of Braga road as a resilience ef ort for the existence of Braga village to survive. Keywords : resilience, urban village, braga, order pattern, adaptation